KEMAMPUAN KONEKSI MATEMATIS DALAM MATERI KUBUS DAN BALOK DIKAJI DARI KREATIVITAS SISWA DI SMP - Permata, Ayunda; Sugiatno, Sugiatno; Ahmad, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to describe mathematical connection ability in materials of cube and cuboid based on junior high school's students' creativities. The aspects that was wanted to be clarified, namely: students' mathematical connection ability are creativity on fluency, flexibility, originality, and elaboration. studied from visual, auditory and kinesthetic learning styles This research measures creativity on four levels: fluency, flexibility, originality, and elaboration. The research method used is descriptive method in the form of case study. Data collection techniques  used are writing test of mathematical connection ability and interview. The subjects of this research are 37 nineth-grade students of SMPN 2 Pontianak. The result showed that students' mathematical connection ability based on creativity's fluency had a percentage of 88.50%, while based on creativity's flexibility had a percentage of 77.70%, creativity's originality had a percentage of 61.40% and creativity's elaboration had a percentage of 39.80%. In the end, it can be deduced that students' mathematical connection ability in materials of cube and cuboid based on junior high school's students' creativities was in the range of good category with percentage of 66.5%.Keywords: Creativity, Mathematical Connection Ability.